Long-Term Outcome of Second-Line Antiretroviral Therapy in Resource-Limited Settings. (July 2014) - Osinusi-Adekanmbi, Olukemi; Stafford, Kristen; Ukpaka, Adiba; Salami, Donald; Ajayi, Samuel; Ndembi, Nicaise; Abimiku, Alash'le; Nwizu, Chidi; Gilliam, Bruce; Redfield, Robert; Amoroso, Anthony
There is limited information on efficacy and durability of second-line antiretroviral therapy (2NL) beyond 12 months in resource-limited settings. A total of 73 patients were enrolled into a prospective 2NL observational cohort in Nigeria. Second-line antiretroviral therapy consisted of lopinavir/ritonavir plus nucleoside reverse transcriptase inhibitors. Time on 2NL ranged from 15 to 31 months. Genotypes were retrospectively done and not available to guide second-line regimen choice. At enrollment, median CD4 count was 121 cells/mm 3, and median time on first-line antiretroviral therapy (1SL) was 24 months. At 6 to 9 months on 2NL, 72.6% (intention to treat [ITT]) and 88.3% (on treatment [OT]) had an undetectable viral load (UDVL). At 12 months, 65.8% (ITT) and 90.57% (OT) had UDVL. At >12 to 24 months and at >24 months, 57.5% (ITT) and 91.3% (OT) had UDVL. No statistically significant association was observed between CD4 at 2NL start, sex, genotypic sensitivity score of 2NL, or tenofovir (TDF) use in 1SL and viral suppression. Two patients developed major protease inhibitor mutations while on 2NL. We observed a high degree of viral suppression at 12 months and little loss of viral suppression thereafter.